Origins : fourteen billion years of cosmic evolution - Tyson, Neil deGrasse (W.W. Norton & Company, 2014)
Drawing on the current cross-pollination of geology, biology and astrophysics, Origins brings to life the thrilling astronomical discoveries of recent years.